2016
DOI: 10.1182/bloodadvances.2016000810
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous leukemia stem cells in myeloid blast phase chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is an excellent model of the multistep processes in cancer. Initiating mutations are required for the initial phase of the disease (chronic phase, CP-CML). Some CP-CML patients acquire additional mutation(s) that transforms CP-CML to poor prognosis, hard to treat, acute myeloid or lymphoid leukemia or blast phase CML (BP-CML). It is unclear where in the hemopoietic hierarchy additional mutations are acquired in BP-CML, how the hemopoietic hierarchy is altered as a consequence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Apart from one report to the contrary 31 , CD34 + CD38cells are generally accepted as the principal immunophenotype in which CP-CML LSCs reside. However, LSCs in BP-CML reside in multiple immunophenotypes normally associated with less primitive hematopoietic cells 32,33 , as well as within the CD34sub-fraction 34 . In this respect, BP-CML mirrors AML, in which LSCs are also found in a variety of CD34 + and CD34immunophenotypes 23,[35][36][37] .…”
Section: [H2] Cell Surface Marker Definitions the Expression Of Cd34mentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from one report to the contrary 31 , CD34 + CD38cells are generally accepted as the principal immunophenotype in which CP-CML LSCs reside. However, LSCs in BP-CML reside in multiple immunophenotypes normally associated with less primitive hematopoietic cells 32,33 , as well as within the CD34sub-fraction 34 . In this respect, BP-CML mirrors AML, in which LSCs are also found in a variety of CD34 + and CD34immunophenotypes 23,[35][36][37] .…”
Section: [H2] Cell Surface Marker Definitions the Expression Of Cd34mentioning
confidence: 99%
“…This is because the vast majority of CML patient samples do not engraft well in immunocompromised mice. The exception to this is in BP-CML, where the proportion of patient samples that engraft is higher than in CP-CML and often at moderate to high levels of chimerism [G] (although cohort sizes in these studies were small) 33,34,57 . For these reasons, it remains challenging to establish correlations between engraftment potential and prognosis in CP-CML or BP-CML.…”
Section: [H2] Cell Surface Marker Definitions the Expression Of Cd34mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a targeted therapeutic approach, disease persistence is driven by a small residual BCR-ABL1 positive (+) stem cell population [5][6][7][8][9]. This can lead to disease progression to the more acute form, termed blast crisis, which carries a very poor prognosis [10]. Measures to enhance the elimination of residual disease are therefore required to further improve outcomes and increase the number of patients obtaining deep molecular remission (DMR; defined as ≥4-log reduction in BCR-ABL transcript levels) who can be considered for discontinuation of TKI treatment and long-lasting treatment-free remission (TFR) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Research around this area is hampered due to the difficulty in isolating true BP-CML LSCs by immunophenotyping. Recent studies in patient-derived xenograft mouse models have shown that engraftable cells exist in all so-called stem and progenitor populations from BP-CML patient samples, usually a preserve of true HSCs in normal samples and CP-CML patient samples (Kinstrie et al, 2016).…”
Section: Epigenetic Mechanisms In CML Disease Progressionmentioning
confidence: 99%